Private equity challenge - investment committee paper - de Longhi - business plan & valuation - Bentes, António Sanches Esteves Correia (2022)
This work project is based on an investment committee paper regarding De’ Longhi, a leading player in the manufacturing of premium small appliances. The paper covers a preliminary analysis of the company and the markets it operates. Based on these capabilities, several value creation strategies were created and builtin to a business plan. The final section of the paper includes returns under different possibles cenarios and insights regarding the exit and due diligence aspects of the paper.